Characterization of four Escherichia albertii isolates collected from animals living in Antarctica and Patagonia - Grillová, Linda; Sedláček, Ivo; Páchníková, Gabriela; Staňková, Eva; Švec, Pavel; Holochová, Pavla; Micenková, Lenka; Bosák, Juraj; Slaninová, Iva; Šmajs, David (The Journal of veterinary medical science, 2018)
Escherichia albertii is a recently discovered species with a limited number of well characterized strains. The aim of this study was to characterize four of the E. albertii strains, which were among 41 identified Escherichia strains isolated from the feces of living animals on James Ross Island, Antarctica, and Isla Magdalena, Patagonia. Sequencing of 16S rDNA, automated ribotyping, and rep-PCR were used to identify the four E. albertii isolates. Phylogenetic analyses based on multi-locus sequence typing showed these isolates to be genetically most similar to the members of E. albertii phylogroup G3. These isolates encoded several virulence factors including those, which are characteristic of E. albertii (cytolethal distending toxin and intimin) as well as bacteriocin determinants that typically have a very low prevalence in E. coli strains (D, E7). Moreover, E. albertii protein extracts caused cell cycle arrest in human cell line A375, probably because of cytolethal distending toxin activity.
Keywords: Antarctic Regions; feces; Antarktida; Ribotyping; pulzní gelová elektroforéza; Multilocus Sequence Typing; Escherichia albertii; RNA ribozomální 16S; Charadriiformes; Electrophoresis, Gel, Pulsed-Field; zvířata; ribotypizace; RNA, Ribosomal, 16S; Feces; Chile; cytolethal distending toxin; Escherichia; Antarctica; bacteriocins; multilokusová sekvenční typizace; polymerázová řetězová reakce; Seals, Earless; Polymerase Chain Reaction; Spheniscidae; Animals; tuleňovití